2019
DOI: 10.3897/popecon.3.e39152
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, economic, geospatial data for municipalities of the Central Federal District in Russia (excluding the city of Moscow and the Moscow oblast) in 2010-2016

Abstract: n/a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Analysis of theoretical concepts describing agglomerations showed that at a certain stage of agglomeration central city development, one or more territorial units (city, urban district), characterized by migration attractiveness, are formed beyond the borders of the ag- Source: Calculated by the author on the basis of the database of indicators for municipalities (Kalabikhina et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of theoretical concepts describing agglomerations showed that at a certain stage of agglomeration central city development, one or more territorial units (city, urban district), characterized by migration attractiveness, are formed beyond the borders of the ag- Source: Calculated by the author on the basis of the database of indicators for municipalities (Kalabikhina et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the change of Moscow and Moscow Oblast borders in 2011-2012, as well as the lack of data on many urban districts of Moscow Oblast (Patsiorkovsky et al 2019) force excluding these regions from the study during the period under review (2011-2016). The database of demographic, economic and geospatial indicators for municipalities of the Central Federal District in Russia (excluding the city of Moscow and the Moscow Oblast) in 2011-2016 serves as the initial data for analysis (Kalabikhina et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the municipal level in the Central Federal District, there is a weak negative correla tion between the number of registered cases of the disease per 100 thousand people (as of May 7) and the share of the population over working age (0.25) (indicators of natural and migration movement in the municipalities of the Central Federal District in previous years are not related to spread of the disease). To calculate the correlation coefficients, data from Rospotrebnadzor and a database of municipalities of the Central Federal District were used (Kalabikhina et al 2019).…”
Section: Spatial Differentiation Of the Pandemic In Russiamentioning
confidence: 99%
“…Change in the population of municipal entities, 2011-2019. Source: Compiled by the author based on Rosstat data,(Kalabikhina et al 2019)…”
mentioning
confidence: 99%